Bacteria on the hands of children inpatients. - Candido de Almeida, Marcela Cristina; Correa, Ione (Investigación y Educación en Enfermería, 2012)
<!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To estimate the prevalence of bacteria isolated in samples from the hands of school-age children at a hospitalization unit. Methodology. In 2009, strains were cultured from the hands of 90 school-age children at the pediatric hospitalization unit of Hospital Estadual Bauru (São Paulo, Brazil). After culture of the samples, the isolated bacteria were identified. Results. In 98% of the samples taken from the children, bacteria were isolated. Coagulase-negative Staphilococcus was isolated in 64% of the samples, followed by Staphilococcus aureus (5%) and Pseudomonas aeruginosa (1%). Conclusion. In most of the samples from the children’s hands, bacteria were isolated. Therefore, educative actions about hygiene habits in- and outside the hospital environment should be reinforced, aimed at children and their companions.